Antioxidant Activity and Consumer Preference of Yoghurt Enriched with Sargassum polycystum Extract - Amir Husni; Maria Madalena; U. Ustadi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Research on the addition of antioxidants to yogurt with ethanolic extract ofSargassum polycystum has been done. This study aims were to determine the effect ofethanolic extract of S. polycystum into the yoghurt to the antioxidant activity and thelevel of consumer acceptance as well as determine the effect of ethanolic extract ofS. polycystum of chemical composition on yoghurt. S. polycystum was extracted usingethanol 96%. The ethanolic extract were inforfified into yoghurt drink and tested theantioxidant activity and the chemical compositionas well as consumer acceptance test.Fermented yoghurt fortified with ethanolic extract of S. polycystum of 0.00; 0.22; 0.44;0.66, 0.88, and 1.10%. The results showed that the addition of ethanolic extract was notsignificant (p>0.05) on pH, but significant (p<0.05) to total lactic acid, antioxidant activity,chemical composition (proximate), and consumer acceptance.Keywords: Antioxidant activity, ethanol cextract, Sargassum polycystum, consumeracceptance, yoghurt